INVENTARISIR PERATURAN MAHKAMAH INTERNASIONAL: MEMAHAMI KEKUATAN DAN PRAKTIKNYA DALAM PENYELESAIAN SENGKETA - Aldo Syahputra; Shifra Sylvania Anandya; Ragil Triokta Handayani; Syakirah Farah Diva; Regina Syafriani Boru Sitorus; Melisya Indriani (Fakultas Hukum Universitas Wiraraja, 2026)
International Criminal Judge rulings have a significant impact on international relations and international law, because UN member states that ratify the Statute of the Court are committed to complying with its decisions. committed to abide by its decisions. The binding nature of the Court's decisions This binding nature of court decisions certainly applies to every decision issued by the International Court of Justice. The International Court of Justice is tasked with resolving disputes between states, as well as providing legal advice to UN bodies and other international organizations. organizations. However, there are still some countries that do not implement the decision of the International Court of (International Criminal Judge). This research explains the ICJ's contingent and advisory jurisdiction, and examines the impact of the Court's decisions on the states involved, both those of the Court's decisions on the states involved, both those that both complying with and ignoring the judgment. Basically, every states that are signatories to the UN Charter and all parties involved in a dispute are obliged to comply with any rulings issued by the Court. disputes are obliged to comply with every decision issued by the IC (Article 94 of the UN Charter). The writing of this article aims to discuss the power of decisions of the International Court of Justice (ICJ) in resolving international disputes and highlight its role in international disputes as well as highlighting its role as the main organ of the United Nations governed by the UN Charter. Through historical analysis and case studies with normative juridical research method and reviewing various international regulations, this article demonstrates the importance of understanding the authority of the international regulations, this article shows the importance of understanding the authority and competence of the ICJ in maintaining peace and resolving conflicts peacefully and peace.